Group Counseling Cognitive Restructuring Techniques To Reduce Student Smoking Behavior - Ramtia Darma Putri; Syska Purnama Sari; Erfan Ramadhani; Nabila Nabila; Beti Arliana (Jurnal Neo Konseling, 2022)
The phenomenon of smoking in Indonesia is very concerning because it has penetrate to school children. Often found in a number of places such as stalls, terminals, or other hangout places, a group of junior high and high school students joking around while competing to smoke cigarettes. Some of the causes of students doing these acts are because they are following their friends, just trying, and to relieve stress, there are even students who have become active smokers. The aim of the researcher is to determine the effectiveness of group counseling with cognitive restructuring techniques in reducing students' smoking behavior. The type of research used is a quantitative pre-experimental design using a one group pretest-posttest design. The population in this study were 68 male students with a sample of 7 students of class XIII. Data collection techniques using questionnaires, documentation, and observation. The results of data analysis showed that the average pre-test result was 64.85 and the post-test average was 44.8. Obtained Zcount = -2,371 with a value of Ztable = 1,645. The results obtained showed a decrease in the average value after the post-test. Based on this, it can be concluded that group counseling with cognitive restructuring techniques is effective or significant in reducing students' smoking behavior.